Produksi bio-oil dan bio-arang dari mata kayu industri pulp melalui pirolisis [Production of bio-oil and bio-char from knot in pulp mill through pyrolysis] - Syamsudin Syamsudin (Jurnal Riset Industri Hasil Hutan, 2019)
Acacia mangium knotis one of the biomass reject produced from the wood chemical pulping processes. This raw material is suitable for the production of bio-oil and bio-char in competitive costs. Utilization of the knot for the production of bio-oil and bio-char makes pulp mill as a bio-refining system with many profitable products because of increased income from bio-oil and bio-char and reduced costs for solid waste disposal. This study aims to evaluate the pyrolysis of knots from the kraft pulp mill to produce bio-oil and bio-char. Pyrolysis experiments of Acacia mangium knotwere carried out using laboratory-scale fluidized bed reactors at 400oC for 30 minutes. Acacia mangium knot contains volatile matterof 69.90% (dried basis) with a calorific value of 4279 kcal/kg (dried basis) has potency to produce bio-oil through the pyrolysis process. The TG-DTG analysis with heating rate of 10oC/min showed the pyrolysis reaction at temperature of 200oC-750oC resulting in a mass decreasing from 90% to 30% or around 85% of total conversion. The yield of bio-oil from fast pyrolysis was about 47%. Bio-oil contains high various organic compounds and dominated by acetic acid (21%) and 2-propanone (28%), and produced bio-char with a calorific value of 5763 kcal/kg (dried basis). Bio-char products could be used as a solid fuel in the combustion process or gasification process.